2012
DOI: 10.1159/000342431
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Relation to Tumor Size in Patients with Hepatocellular Carcinoma

Abstract: tients had more advanced portal hypertension with thrombocytopenia than did larger-tumor patients. Tercile I patients with higher AFP levels had more frequent PV thrombosis and worse survival than those with lower AFP levels. Elevated serum GGTP and ALKP levels appear to be associated with a more aggressive HCC phenotype. These differing patterns suggest more than one HCC pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…This is in line with other studies showing an association of thrombocytopenia and smaller tumor size when compared to patients with higher platelet counts [40][41][42]. Pathophysiologically, it was shown that platelets play a proinflammatory role in the course of chronic liver disease.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with other studies showing an association of thrombocytopenia and smaller tumor size when compared to patients with higher platelet counts [40][41][42]. Pathophysiologically, it was shown that platelets play a proinflammatory role in the course of chronic liver disease.…”
Section: Discussionsupporting
confidence: 91%
“…Thrombocytopenia is a risk for HCC in predisposed patients (3, 1215), and associated with small HCC size (16, 17). We combined terciles II and III to create a manageable large tumor category for this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thrombocytopenia is a cirrhosis surrogate, an HCC risk factor, prognostic factor, and is associated with small HCCs (713, 16, 17). Non-cirrhotic HCCs can be large (22, 23, 24), and associated with thrombocytosis (25), which is a general sign of early malignancy (26).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative PLT was negatively associated with the amount of transfused platelets during surgery (coefficient -0.49; P < 0.001), during the first week after surgery (coefficient -0.55; P < 0.001), and between 1 and 2 weeks after surgery (coefficient -0.21; P < 0.001). Accordingly, the amount of transfused platelets during surgery, during the first week after surgery, and between 1 and 2 weeks after surgery was 0 (0-6), 9 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and 0 (0-0) units in the low platelet group and 0 (0-0), 0 (0-4), and 0 (0-0) units in the high platelet group, respectively, where 1 unit of apheresis platelets was considered to be equivalent to 6 units of platelets, as described previously. (22) Minimum PLT measured at each postoperative day during the first 2 weeks after transplantation was consistently <30 3 10 9 /L in median within the subgroup of recipients who underwent platelet transfusion on each corresponding day, indicating that platelet transfusion was performed according to our standardized protocol targeting PLT >30 3 10 9 /L (Supporting Fig.…”
Section: Association Between Perioperative Plt and Platelet Transfusionmentioning
confidence: 99%
“…(8) Another retrospective cohort study demonstrated that pretreatment PLT was positively associated with the probability of HCC recurrence after curative treatment. (9) The relationship between platelets and tumors is not a simple epiphenomenon resulting from tumor-induced thrombopoiesis, but rather a direct contribution of platelets to multiple steps in the cancer progression, including tumor cell angiogenesis, protection from immune attack, extravasation, and arrest within the vasculature.…”
mentioning
confidence: 99%